Endoscopic submucosal dissection of 301 large colorectal neoplasias: outcome and learning curve from a specialized center in Europe - Rönnow, Carl-Fredrik; Uedo, Noriya; Toth, Ervin; Thorlacius, Henrik (Endoscopy International Open, 2018)
Background and study aims Endoscopic submucosal dissection (ESD) allows en bloc resection of large colorectal lesions but ESD experience is limited outside Asia. This study evaluated implementation of ESD in the treatment of colorectal neoplasia in a Western center.Patients and methods Three hundred and one cases of colorectal ESD (173 rectal and 128 colonic lesions) were retrospectively evaluated in terms of outcome, learning curve and complications. Results Median size was 4 cm (range 1 – 12.5). En bloc resection was achieved in 241 cases amounting to an en bloc resection rate of 80 %. R0 resection was accomplished in 207 cases (69 %), RX and R1 were attained in 83 (27 %) and 11 (4 %) cases, respectively. Median time was 98 min (range 10 – 588) and median proficiency was 7.2 cm2/h. Complications occurred in 24 patients (8 %) divided into 12 immediate perforations, five delayed perforations, one immediate bleeding and six delayed bleedings. Six patients (2 %), all with proximal lesions, had emergency surgery. Two hundred and four patients were followed up endoscopically and median follow-up time was 13 months (range 3 – 53) revealing seven recurrences (3 %). En bloc rate improved gradually from 60 % during the first period to 98 % during the last period. ESD proficiency significantly improved between the first study period (3.6 cm2/h) and the last study period (10.8 cm2/h).Conclusions This study represents the largest material on colorectal ESD in the west and shows that colorectal ESD can be implemented in clinical routine in western countries after appropriate training and achieve a high rate of en bloc and R0 resection with a concomitant low incidence of complications. ESD of proximal colonic lesions should be attempted with caution during the learning curve because of higher risk of complications.